2018
DOI: 10.5937/fmet1802157z
|View full text |Cite
|
Sign up to set email alerts
|

Fracture development and deformation behavior of zeolite-filled high density polyethylene annealed composites in the plane stress fracture

Abstract: This study explores the zeolite-high-density polyethylene (HDPE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
1
Order By: Relevance
“…It is also shown that long-term UV radiation can cut off the polymer chains which can ultimately alter crystallinity and other mechanical properties. Cell interactions can be increased by diversified the molecular weight [147,148]. Matsuhira [146] reported that the density of silkworm bands observed using SDS-PAGE is decreased with increasing UV irradiation times.…”
Section: (Lm W) (H M W) (H Ima Rk ) N C La Va T a B M Orimentioning
confidence: 99%
“…It is also shown that long-term UV radiation can cut off the polymer chains which can ultimately alter crystallinity and other mechanical properties. Cell interactions can be increased by diversified the molecular weight [147,148]. Matsuhira [146] reported that the density of silkworm bands observed using SDS-PAGE is decreased with increasing UV irradiation times.…”
Section: (Lm W) (H M W) (H Ima Rk ) N C La Va T a B M Orimentioning
confidence: 99%
“…In previous works [25,26] it has been reported that the skull implant material from zeolite-HDPE composites has good fracture toughness but its fracture behavior tends to be brittle. This fracture behavior must be given serious attention so that the problem of brittle fracture can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…This fracture behavior must be given serious attention so that the problem of brittle fracture can be avoided. This work is intended as a response to previous works conducted by Purnomo and co-workers [25,26] related to the improvement of the fracture toughness behavior of Z/HDPE composites used to the skull bone implants application. In this work, chopped silk fiber (SF) was added to the zeolite/HDPE composite as a reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, zeolites, a class of silica-based porous materials, was chosen as a source of silica by considering its non-toxicity, large surface area, modifiable porosity, and high mechanical strength [30][31][32][33][34][35]. In earlier work, it was reported that zeolites have been widely applied in artificial bone engineering that can reliably improve the quality of bone tissue repair [36].…”
Section: Introductionmentioning
confidence: 99%